Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Family Raya Gurun Laweh Padang - Rahmasari Rahayu Putri; Nadila Dwi Arista; Diva Armenita; Andry Novrianto (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research aims to examine the effect of work motivation on employee performance. The respondents consisted of 100 permanent employees at PT. Family Raya Gurun Laweh Padang, Padang City. In this study, we used a quantitative method in the form of a questionnaire as one of the data collection techniques. Data analysis used regression methods. The success of a company can be achieved by improving employee performance. Overall, this study proves that work motivation is one of the main factors influencing employee performance at PT. Family Raya Gurun Laweh Padang. With a contribution of 62%, the company can focus on motivation enhancement strategies to achieve organizational targets more effectively. However, further research is needed to identify other factors that also influence performance so that the company can develop a more comprehensive human resource management approach.